(untitled) (Homoeopathy for All, 2025)
Background: Hemorrhoids are a common anorectal condition resulting from the pathological enlargement and distal displacement of anal vascular cushions. Conventional treatments vary from conservative management to surgical intervention. Individualized homeopathic prescribing is frequently used in clinical practice for symptomatic relief and long term management. Case Summary: A 45-year-old female presented with chronic constipation, painful defecation, marked straining, and bleeding per rectum for several months. Examination indicated Grade II internal hemorrhoids. The patient also reported congestion of the pelvic region, a sensation of incomplete evacuation, and severe rectal pain following stool. Based on a detailed case analysis, Collinsonia canadensis was prescribed in its individualized potency. Results: Significant improvement in pain, bleeding, and straining was observed within two weeks. Follow up over three months showed complete resolution of symptoms and normalization of bowel habits without recurrence. Conclusion: This case demonstrates the potential role of individualized homeopathic prescribing—specifi cally Collinsonia canadensis—in the management of Grade II hemor rhoids. Further studies with larger sample sizes are recommended.